NASKAH DRAMA SENJA DENGAN DUA KELELAWAR KARYA KRIDJOMULYO: KAJIAN PSIKOLOGI SASTRA DAN RELEVANSINYA SEBAGAI BAHAN AJAR APRESIASI DRAMA DI SEKOLAH MENENGAH ATAS - Akbar Bagus Wicaksono; Ani Rakhmawati; Raheni Suhita (Universitas Sebelas Maret, 2018)
This research aims to explain: (1) characters character in the drama script Senja Dengan Dua Kelelawar; (2) the inner conflicts experienced by the characters in the drama script Senja Dengan Dua Kelelawar; and (3) the relevance of the drama Senja Dengan Dua Kelelawar as a teaching material for drama appreciation at senior high school. This study uses a literature psychology study, which uses a psychological approach to knowing the character of the character through observation of behavioral characters. The results of this study are descriptions of: (1) the characterization of the characters in the Drama Senja Dengan Dua Kelelawar which differ from each character. This is done to build a storyline that matches the theme of the drama script; (2) the inner conflicts experienced by the characters in the drama drama Senja Dengan Dua Kelelawar are very complex. Every inner conflict experienced by a character can be described through psychoanalytic theory with a focus on the study of the id, ego, and superego; and (3) the relevance of the Drama of Senja Dengan Dua Kelelawar as a teaching material for drama appreciation in high schools by paying attention to aspects of language, students' psychological development, and cultural background.